2018
DOI: 10.1136/bmj.k4231
|View full text |Cite
|
Sign up to set email alerts
|

Surgical mesh and patient safety

Abstract: A mandatory device registry is long overdue

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“… 55 It has also been suggested that a publicly accessible registry of licensed mesh devices with details of the marketing authorisation and linked evidence would provide useful information on the characteristics and performance of these devices. 56 57 …”
Section: Discussionmentioning
confidence: 99%
“… 55 It has also been suggested that a publicly accessible registry of licensed mesh devices with details of the marketing authorisation and linked evidence would provide useful information on the characteristics and performance of these devices. 56 57 …”
Section: Discussionmentioning
confidence: 99%
“…In their editorial, Heneghan and Godlee refer to NICE guidance as “ineffectual,”3 and we agree that it should have had more impact. Of course, responsibility for implementing guidance does not rest with NICE but requires a system-wide approach.…”
mentioning
confidence: 84%
“…12 Patients often turn to the independent sector for new surgical procedures that are not available on the NHS and overenthusiastic adoption of new techniques by surgeons for financial gain risks scandals such as those associated with breast implants and vaginal mesh. 13 In contrast to medicines, many surgical innovations are introduced without adequate clinical trial or long-term follow-up data and industry is partly to blame for financial inducements to use their products. The RCSEng is calling for all new surgical procedures and devices to be registered, with data collected in appropriate national audits before they are routinely offered to patients, and all adverse incidents reported to the MHRA.…”
Section: New Procedures and Devicesmentioning
confidence: 99%